EVALUASI KUALITAS AIR WADUK BERDASARKAN PARAMETER FISIKA - Erwin Gustianta; Rachmasari Pramita Wardhani (Mechanical Engineering Departement - Universitas Tridharma, 2020)
Reservoir is a large building made by humans by damming a river (Wetzel, 2001). Reservoirsare also an intermediate system between rivers (lotic waters) and lakes (lentic waters). Themanufacture of reservoirs generally has objectives and functions, one of which is for raw water needsfrom drinking water treatment. MG Reservoir is the main source of raw water for PDAM BalikpapanCity. MG Reservoir is a very important aquatic resource in terms of its ecological and economicfunctions. Therefore it must be maintained both in terms of quantity and quality. With the existence ofvarious human activities around MG Reservoir, it will affect the condition of the reservoir. Keywords— evaluation, quality, physics, temperature, transparency, electrical conductivity